Variation in Antioxidant Activity and Antioxidant Constituents of Thymus Serpyllum L Grown in Different Climatic Conditions of Uttarakhand Himalayas - Goyal, Shweta; Pandey, H.K.; Guleria, Kritika; Tewari, Geeta (Defence Life Science Journal, 2021)
In-vitro antioxidant activity of therapeutically important plant Thymus serpyllum L. grown at different altitudes viz. foothill areas, lower Himalayan and higher Himalayan regions were evaluated against various radicals such as DPPH, ABTS and reducing power assays. The antioxidant constituents like total phenols, flavonoids and total tannins were also evaluated in the present study. The results revealed that the alcoholic, as well as the aqueous extracts of the plant, showed significant antioxidant potential against all the radicals. Extracts obtained from different altitude cultivation showed variation in IC50 values. The alcoholic and aqueous extracts prepared from the plants grown at foothill areas (Haldwani) showed the highest DPPH (IC50: ALC-0.566 mg/ml; AQ- 0.778 mg/ml), ABTS (IC50: ALC- 0.484 mg/ml; AQ- 0.533 mg/ml) and reducing power (EC50: ALC- 0.29 mg/ml; 0.42 mg/ml) activities, followed by high altitude cultivated plants, (Auli), with moderate antioxidant activity. The extracts from mid-altitude cultivation (Pithoragarh) exhibited the least antioxidant potential. The results showed that the amount of total phenolics and flavonoids were significantly correlated to the antioxidant activity. Higher the value of phenolics (TS3: 12.63mg CE/g> TS1: 11.51 mg CE/g> TS2: 10.70 mg CE/g) and flavonoids (TS3: 9.30 mg QE/g> TS1: 9.07mg QE/g> TS2: 6.59mg QE/g) in the extracts, greater was the antioxidant activity. Therefore, T. serpyllum grown in foothill areas was more beneficial in preparing various herbal formulations.